Pengembangan Media Pembelajaran Berbasis Flash pada Materi Bilangan untuk Anak Tunarungu Kelas V - Nur Alfa Arniansyah; Syaiful Hamzah Nasution (Jurnal Tadris Matematika, 2021)
This study aims to develop flash-based learning media for whole numbers and fractions for deaf children of class V that are valid, practical, and effective in training students to be skilled in solving whole number and fraction problems. The learning media is equipped with a video using SIBI (Indonesian Sign Language System) to make it easier for deaf students to understand the content of the media. This research using 6 stages referring to the Luther-Sutopo development model, namely: concept, design, material, collection, assembly, testing, and distribution. The instruments in this development research were the media validation sheet and the student response questionnaire sheet. The results of the development research are: (1) there are no misconceptions and all media functions can run well and the media validation score is 4.63 so that the media developed is valid, (2) the student response questionnaire is declared valid with a score of 4.73 so that it can be used in the study, (3) the media practicality score after being tested was 4.74 so that the media was declared practical, (4) 75% of students obtained a KKM score, this shows that students are skilled in solving whole number and fraction problems, so the media is said to be effective.